دراسة هلم لغويا ونحويا وصرفيا واختلاف العلماء فيها - أبو جري، عدنان خلف قليل (جامعة الزقازيق - كلية الآداب, 2006)
درس البحث المسائل المتعلقة بـ هلم لغويا ونحويا وصرفيا، وعرض لاختلاف العلماء فيها فبين أنها استعملت في اللغة بمعنيين، أحدهما أنها بمعني تعال أو احضر، وهي في هذه الحال لازمة، وثانيهما أنها بمعني هات أو قدم، وهي في هذه الحال متعدية. وقد جاءت على هيئتين؛ الأولى: استعمالها بلفظ واحد مع جميع ما تسند إليه من ضمائر الرفع التي للخطاب، وهذه لغة أهل الحجاز، والثانية: استعمالها متصلة بالضمائر بحسب أحوال المخاطبين، وهذه لغة تميم. وناقش البحث الخلاف في مسألة التركيب والبساطة، ومسألة الاسمية والفعلية، فعرض أقوال النحاة في ذلك، ثم رجح ما رآه راجحاً. وقد انتهت الدراسة بخاتمة ذكرت فيها النتائج التي توصل إليها البحث. The present study examines the Arabic word halumma’ from linguistic, syntactic and morphological points of view. It surveys the opinions of different scholars concerning the subject, pointing out that the word is used to denote two meanings: the first, “Come” or! “Come on”, where it is intransitive; while the second is “Bring!” or “Give me!”, where it is transitive. Also the word comes in two forms: first, in the Hijazi dialect, it appears in one fixed form regardless of any subjective second person pronouns it refers to. The second form is in the Tamimi dialect where it appears with pronouns attached to it according to the addressee. Moreover, the study discusses the issues of combination and simplicity, nominalization and verbalization, expounding the views of the different grammarians and preponderating what the researcher has found has found to be preponderant. The study concludes with a summary of its findings.
Keywords: النحاة العرب -- كلمة هلم -- الدلالات اللغوية -- اللغة العربية -- المعاجم العربية -- اللغويون العرب -- الحجازيون -- التميميون -- معاني الألفاظ